Vaginitis Gonorrhea on Children: A case series - Qaira Anum; Heffi Anindya Putri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Background: Vaginitis gonorrhea is sexually transmitted infections (STIs) which caused by Neisseria gonorrhoeae and commonly found in children. Frequently, it indicates the sexual abuse in children. Although infrequent, nonsexual gonorrhea transmission, either from fomites, physical contact or autoinoculation may occur in children. Case report: Three cases of vaginitis gonorrhea on 3, 6 and 8 years old girl with a chief complaint of vaginal discharge that felt no itchy are presented. The history of sexual intercourse or abuse in two cases were denied but they had history of sharing baths and public swimming pool. In one case, there was alleged sexual abuse 6 months ago by her cousin. Physical examination revealed the yellowish odor vaginal discharge and there were no signs of inflammation around they genitalia. There were Gram-negative diplococcal intra and extra cellular. All of Thayer Martin culture revealed a positive result of Neisseria gonorrhoeae. Only one patient performed screening for the other STI, while two patient refused. All of these patients were treated with 125 mg intramuscular ceftriaxone injection but only 1 patient improvement, while 2 others recovered with alternative therapy based on the results of sensitivity test. Discussion : Patients were diagnosed as vaginitis gonorrhea based on physical examination and laboratory results. One case was suspected as sexual abuse while the other were suspected of non-sexual abuse such as fomite. The limitation of this case report are unidentified sources of gonococcal transmission and rejection for completed STIs screening.